1998
DOI: 10.1099/0022-1317-79-12-2929
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three co-circulating genotypes of the small hydrophobic protein gene of mumps virus.

Abstract: Eighteen virus isolates and 22 serum samples collected between 1971 and 1997 from patients with mumps were genotyped by PCR with specific primer pairs for the A, C and D genotypes of the small hydrophobic (SH) protein gene. All serum samples were subjected to nucleotide sequence analysis of the gene, and the deduced 57-aminoacid sequences were aligned with previously published sequences from the USA, Canada,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…Several epidemiological studies reported that some genotypes (C, D, H, I, or J) were able to cause central nervous system (CNS) diseases (20,28,(34)(35)(36)38). Mongolian MuVs belong to genotype H, and all originated from the hospitalized mumps patients.…”
Section: Mumps Epidemics In Mongoliamentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies reported that some genotypes (C, D, H, I, or J) were able to cause central nervous system (CNS) diseases (20,28,(34)(35)(36)38). Mongolian MuVs belong to genotype H, and all originated from the hospitalized mumps patients.…”
Section: Mumps Epidemics In Mongoliamentioning
confidence: 99%
“…For instance, genotypes A, C, D, E, and H are mainly observed in the Western Hemisphere (1,2,13,34), whereas genotypes B, F, and I are solely detected in Asia (16,28,30,42). Some studies have reported the potential associations between genotypes C, D, H, I, or J and neuropathogenicity (28,35,36,38).…”
mentioning
confidence: 99%
“…Several studies report that a correlation between genetic variation and virulence among MuV strains (2,13,14). A relationship between viral genotype and clinical symptoms was also reported (19). The relevance of MuV genotypes G, H, and K to particular clinical features is still unclear.…”
mentioning
confidence: 99%
“…Finally, previous experience with the elimination programs for other preventable viral diseases, such as measles, rubella, and polio, suggest that genotyping would facilitate mumps surveillance (38), since the pattern of viral circulation can be traced. Consequently, molecular epidemiology studies have been performed around the world (2,7,10,11,12,15,17,18,23,31,32,33,34,35,41).Mumps vaccination was introduced in the Spanish national vaccination repertoire in 1981 as part of the triple viral vaccine (the MMR vaccine). As a result, the number of mumps cases fell from 286,887 in 1984 to 1,527 in 2004.…”
mentioning
confidence: 99%